2022
DOI: 10.3390/ijerph19020850
|View full text |Cite
|
Sign up to set email alerts
|

Process Optimization of Electrochemical Treatment of COD and Total Nitrogen Containing Wastewater

Abstract: In this work, an electrochemical method for chemical oxygen demand (COD) and total nitrogen (TN, including ammonia, nitrate, and nitrite) removal from wastewater using a divided electrolysis cell was developed, and its process optimization was investigated. This process could effectively relieve the common issue of NO3−/NO2− over-reduction or NH4+ over-oxidation by combining cathodic NO3−/NO2− reduction with anodic COD/NH4+ oxidation. The activity and selectivity performances toward pollutant removal of the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…As seen in Figure 5 a, the NH 3 -N concentration of sample I and sample II decreased from 853 ± 61 mg/L and 684 ± 48 mg/L to 296 ± 28 mg/L and 359 ± 22 mg/L in 120 min of EO treatment, respectively. The same conclusion should be drawn with COD and TOC results, that is, EO treatment by Ti 4 O 7 anode is more suitable for the pretreatment of wastewater containing high-concentration NH 3 -N. Previous studies have found that the indirect oxidation by HClO generated in EO system and deprotonation by hydroxyl ions on anode contributed to the removal of ammonia [ 34 , 35 , 36 , 37 , 38 ].…”
Section: Resultssupporting
confidence: 60%
“…As seen in Figure 5 a, the NH 3 -N concentration of sample I and sample II decreased from 853 ± 61 mg/L and 684 ± 48 mg/L to 296 ± 28 mg/L and 359 ± 22 mg/L in 120 min of EO treatment, respectively. The same conclusion should be drawn with COD and TOC results, that is, EO treatment by Ti 4 O 7 anode is more suitable for the pretreatment of wastewater containing high-concentration NH 3 -N. Previous studies have found that the indirect oxidation by HClO generated in EO system and deprotonation by hydroxyl ions on anode contributed to the removal of ammonia [ 34 , 35 , 36 , 37 , 38 ].…”
Section: Resultssupporting
confidence: 60%
“…Figure 4(a) shows that the removal efficiency of COD and TN increased with increased degradation time, reaching 64.88 and 67.77% respectively at 12 h, with obvious degradation effect. In the first 8 h of degradation, the removal efficiency of COD and TN were similar, because the initial stage of degradation of pesticide wastewater mainly formed small molecular compounds by breaking bonds of large rings, and only a small amount of CO 2 and NH 4 þ were produced (Yao et al 2022). In the next 10-40 h, the removal rate of TN was higher than that of COD, which may be due to the fact that the concentration of COD in the pesticide wastewater was much higher than that of TN, so that TN was consumed faster.…”
Section: Degradation Of Pesticide Wastewatermentioning
confidence: 91%
“…In addition, the MEBD system had the highest removal rate of TN. Although the DB had higher activity and faster denitrification rate under alkaline condition (pH = 8) [14], the reduction rate of nitrate nitrogen decreased due to the decrease of Fe 2+ production rate in micro-electrolysis reaction [22]. Furthermore, the presence of activated carbon might reduce the pH of the water [23].…”
Section: Effect Of Phmentioning
confidence: 99%
“…In addition, Fe 0 and Fe 2+ formed by electrode corrosion reduced a portion of NO 3 − -N to NH 4+-N[54] and then the oxidation reaction occurred on the anode to generate NO 3 − /NO 2 − . Meanwhile, the NO 3 − /NO 2 − as the over-oxidation by-product of NH 4 + could be recirculated into the cathode and continuously reduced to N 2[22].…”
mentioning
confidence: 99%